Kontrak lisensi: sarana pengembangan teknologi dan hak atas kekayaan intelektual di Indonesia - Widihastuti, Setiati (Jurnal Civics: Media Kajian Kewarganegaraan, 2009)
The urgenry of information technology for all aspects of lofe is not merelY a discourse. The necessity of modern and global activities requires renewal of technology is inevitable. Consequently there will be a new invention, mobilization and transformation. The phenomenon can enhance globalization of intellectual rights. Because of its urgency, present information technol ogy threatens to intellectual works protected with patents or trade mark (brand). License is not onlYyan alternative to fulfill renewal of information technology, but also to protect the ’’owners’’ of the technology. Through license contract, licensor basicallY permits licensee to utilize the technology possessed As return the licensor receives royalties. In fact, imbalanced bargaining position and free/ unlimited contract are often used by licensor to ’force" a restrictive trade clause which potentiallY limits licensee’s freedom as technology receivers. Therefore it is necessary to confirm in goodwill for involved parties as good conduct to license contract making.